Spinal Cord Imaging Markers and Recovery of Volitional Leg Movement With Spinal Cord Epidural Stimulation in Individuals With Clinically Motor Complete Spinal Cord Injury - Rejc, Enrico; Smith, Andrew C.; Weber, Kenneth A.; Ugiliweneza, Beatrice; Bert, Robert J.; Negahdar, Mohammadjavad; Boakye, Maxwell; Harkema, Susan J.; Angeli, Claudia A. (Frontiers in Systems Neuroscience, 2020)
Previous studies have shown that epidural stimulation of the lumbosacral spinal cord (scES) can re-enable lower limb volitional motor control in individuals with chronic, clinically motor complete spinal cord injury (SCI). This observation entails that residual supraspinal connectivity to the lumbosacral spinal circuitry still persisted after SCI, although it was non-detectable when scES was not provided. In the present study, we aimed at exploring further the mechanisms underlying scES-promoted recovery of volitional lower limb motor control by investigating neuroimaging markers at the spinal cord lesion site via magnetic resonance imaging (MRI). Spinal cord MRI was collected prior to epidural stimulator implantation in 13 individuals with chronic, clinically motor complete SCI, and the spared tissue of specific regions of the spinal cord (anterior, posterior, right, left, and total cord) was assessed. After epidural stimulator implantation, and prior to any training, volitional motor control was evaluated during left and right lower limb flexion and ankle dorsiflexion attempts. The ability to generate force exertion and movement was not correlated to any neuroimaging marker. On the other hand, spared tissue of specific cord regions significantly and importantly correlated with some aspects of motor control that include activation amplitude of antagonist (negative correlation) muscles during left ankle dorsiflexion, and electromyographic coordination patterns during right lower limb flexion. The fact that amount and location of spared spinal cord tissue at the lesion site were not related to the ability to generate volitional lower limb movements may suggest that supraspinal inputs through spared spinal cord regions that differ across individuals can result in the generation of meaningful lower limb volitional motor output prior to any training when epidural stimulation is provided.